2020
DOI: 10.21203/rs.3.rs-31248/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addressing the Problems and Challenges of Medical Research During the Syrian Crisis

Abstract: Introduction : The Syrian crisis started 9 years ago causing substantial damage to the country’s infrastructure, and the consequences of this tragedy have further stunted the underdeveloped research environment in Syria. This paper aims to address the challenges of conducting medical research among Syrian academics during the Syrian crisis. Methods: The data were collected from (471) Syrian researchers (MsC or PhD students, university professors) from 13 universities and hospitals, covering 10 governates. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…10,11 A recent report about the problems and challenges of medical research in Syria demonstrated that the most important barriers were the limited financial support and research equipment and the lack of research-related skills. 12 Another report shed light on comparable results from undergraduate students at Damascus University. 13 However, there is a lack of comprehensive evidence regarding research productivity of postgraduate medical personnel.…”
Section: Introductionmentioning
confidence: 94%
“…10,11 A recent report about the problems and challenges of medical research in Syria demonstrated that the most important barriers were the limited financial support and research equipment and the lack of research-related skills. 12 Another report shed light on comparable results from undergraduate students at Damascus University. 13 However, there is a lack of comprehensive evidence regarding research productivity of postgraduate medical personnel.…”
Section: Introductionmentioning
confidence: 94%
“…A recent report about the problems and challenges of medical research in Syria demonstrated that the most important barriers were the limited nancial support, the lack of research-related skills, the lack of research equipment and the absence of stable internet and electricity [11]. Another report shed light on the attitudes, barriers, and practices of medical research among medical students in Damascus University and had found comparable results [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, the most important barriers were the limited nancial support, the lack of researchrelated skills, the lack of research equipment and the absence of stable internet and electricity (12).…”
Section: Introductionmentioning
confidence: 99%